1994
DOI: 10.1093/oxfordjournals.annonc.a058979
|View full text |Cite
|
Sign up to set email alerts
|

Biochemotherapy with thymosin α1, interleukin-2 and dacarbazine in patients with metastatic melanoma: Clinical and immunological effects

Abstract: The combination of DTIC + TA1 + IL-2 is active in the treatment of advanced melanoma, with acceptable toxicity. However, even more active regimens are needed, and the interactions between thymic hormones and cytokines should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Consistent with the results of previous studies [29][30][31][32][33], our results suggest an association between thymalfasin therapy and restored immune function. In the current trial, patients who received thymalfasin in addition to TACE experienced no bacterial infections versus those who received TACE alone, among whom there were four infections including sepsis, cholecystitis, and bacterial peritonitis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the results of previous studies [29][30][31][32][33], our results suggest an association between thymalfasin therapy and restored immune function. In the current trial, patients who received thymalfasin in addition to TACE experienced no bacterial infections versus those who received TACE alone, among whom there were four infections including sepsis, cholecystitis, and bacterial peritonitis.…”
Section: Discussionsupporting
confidence: 93%
“…Thymalfasin promotes T-cell differentiation, enhances cytokine (IFN-c, IL-2, IL-3) production, and downregulates T-cell apoptosis [15][16][17][18][19][20][21][22][23]. It has been shown to decrease tumor cell growth both in vitro and in vivo [24][25][26][27][28] and has demonstrated therapeutic usefulness in several types of cancer, including non-small cell lung cancer and malignant melanoma [29][30][31]. One phase II study has been completed that examined the efficacy and safety of thymalfasin for the treatment of HCC [32].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that the decapeptide spanning residues 100-109 of proT 's carboxy-terminus (proT (100-109); TKKQK TDEDD) is the actual immunoactive area of the polypeptide and a most potent lymphocyte stimulator [89]. ProT (100)(101)(102)(103)(104)(105)(106)(107)(108)(109) induces PBMC proliferation and cytotoxicity, promotes the maturation of dendritic cells (DC), adopts a -sheet conformation, and its eVects are sequence-speciWc and comparable to that of intact proT . In an earlier study, we had shown that a slightly smaller segment (103)(104)(105)(106)(107)(108)(109) was also eVective in restoring the immune function of PBMC obtained from cancer patients in vitro [90].…”
Section: A-thymosins In Cancer Therapymentioning
confidence: 99%
“…The Wrst was conducted in 1985 by the group of Alan Goldstein [101], where in post-irradiated non-small cell lung (NSCL) cancer patients (42 individuals), administration of T 1 (900 g/m 2 /day) for 14 days showed normalization or maintenance of normal CD4+ T cell percentages and improvement of relapse-free and overall survival. Several years later in 1994 [102], patients with metastatic melanoma (46 in total) were treated with dacarbazine (DTIC), followed by 2 s.c. doses of T 1 (2 mg/dose) and IL-2. Complete response was recorded in 2 patients and stable disease in 5, median survival was 11 months, and the toxicity of the regimen was acceptable.…”
Section: A-thymosins In Cancer Therapymentioning
confidence: 99%
“…Two small pilot studies showed beneficial effects compared to historical control when Ta1 treatment was added to Dacarbazine (DTIC) chemotherapy combined with IL-2 [165] or IFN-alpha [166].…”
Section: Melanomamentioning
confidence: 99%